The effect of part-time work on post-secondary educational attainment: New evidence from French data - Magali Beffy; Denis Fougère; Arnaud Maurel (Institute for the Study of Labor (IZA), 2010)
In this paper, we provide new evidence on the effect of part-time work on postsecondary educational attainment. To do so, we use samples extracted from the French Labor Force Surveys conducted over the years 1992-2002. These samples are restricted to students in initial education following university studies and preparing an Associate, a Bachelor or a Master degree. We estimate probit models with two simultaneous equations accounting for part-time working while studying and for success on the final exam, along with the decision to continue the following year in one of the models. We take the working time into account by drawing in one of the models a distinction between jobs in which more or less than 16 hours are worked per week. We use variations across departements in low-skilled youth unemployment rates and in their interactions with the father's socio-economic status in order to identify the effect of part-time work on educational attainment. Our results suggest a statistically significant and very large detrimental effect of holding a regular part-time job on graduation probability. Still, a complementary analysis shows that working while studying does not have any significant effect on the probability of continuing studies.
Keywords: C35; I20; J24; 330; post-secondary educational attainment; students' labor supply; bivariate Probit models; Studierende; Befristeter Arbeitsvertrag; Studium; Bildungsabschluss; Jugendarbeitslosigkeit; Sozialer Status; Schätzung; Frankreich